Association of tricuspid regurgitation within normal range on the development of left ventricular diastolic dysfunction in patients with uncomplicated hypertension. (4th May 2018) - Iida, Masato; Yamamoto, Mitsuru; Ishiguro, Yuko; Honjo, Haruo; Kamiya, Kaichirou
Abstract: Aim: Tricuspid regurgitation (TR) with the maximum velocity >2.8m/s has been newly integrated into the diagnostic criteria for left ventricular (LV) diastolic dysfunction. Although the maximum velocity of TR within the normal range (TR < 2.8m/s) is frequently detected in hypertensive patients and is associated with enlarged left atrial (LA) volumes, the influence of TR < 2.8m/s on LV diastolic dysfunction remains unknown in uncomplicated hypertension. Methods: Echocardiography was performed to assess the mitral annular velocity (e'), E/e', LV mass, and LA phasic volumes and emptying fractions (total, passive, and active) in 100 patients with uncomplicated hypertension with TR within the normal range and in 77 of those without measurable TR. Patients were defined as having normal, inclusive, or dysfunction of LV diastolic function, according to how many parameters met the cut-off levels (maximum LA volume index >34ml/mm 2, e'<7 cm/s, and E/e'>15). Pulmonary artery systolic pressure (PASP) was estimated by the formula; PASP =4 (maximum velocity of TR) 2 + 5 mmHg. Results: The maximum velocity of TR or PASP saw a positive correlation, and LA total or passive emptying fractions saw an inverse correlation with LV diastolic dysfunction in hypertensive patients with TR < 2.8. In contrast, pulse pressure and LV mass saw positive correlation in hypertensive patients without TR. A stepwise ordinal logistic regression analysis indicated that PASP and LA passive emptying fractions were associated with LV diastolic dysfunction in hypertensive patient with TR < 2.8m/s. Conclusion: The presence of TR may be related to the development of LV diastolic dysfunction in hypertensive patients with TR <2.8m/s.